Detection and characterization of Cucumber mosaic virus (CMV) infecting turmeric (Curcuma longa L.) in Malaysia - Buhari, Muhammad; Kong, Lih Ling; Lau, Wei Hong; Vadamalai, Ganesan (-, 2021)
Turmeric (Curcuma longa L.) is among the herbs cultivated in Malaysia, and it is of agricultural, medicinal and socioeconomic importance. Cucumber mosaic virus (CMV) has been reported in vegetables, ornamental crops and weed hosts in Malaysia, thus, denoting the long existence of the pathogen in the agroecosystem of the country.